Kinematics and EMG analysis of expert pole vaulter's lower limb during take off phase - Bassement, M.; Garnier, C.; Lepoutre, F.-X.; Sampson, M. G. (The Engineering of sport 7, Volume 2, 2008)
Introduction: The critical phase, in jumping events in track and field, appears to be between touchdown and take-off. Since obvious similarities exist between the take off phase in both long jump and pole vault, numerous 3D kinematics and electromyographic studies have only looked at long jump. Currently there are few detailed kinematics electromyographic data on the pole vault take-off phase. The aim of this study was therefore to characterise kinematics and electromyographic variables during the take-off phase to provide a better understanding of this phase in pole vaulting and its role in performance outcome. Material and methods: Six pole-vaulters took part in the study. Kinematics data were captured with retro reflective markers fixed on the body. Hip, knee and ankle angle were calculated. Differential bipolar surface electrodes were placed on the following muscles of the take-off leg: tibialis anterior, lateral gastrocnemius, vastus lateralis, rectus femoris , bicep femoris and gluteus maximus. EMG activity was synchronously acquired with the kinematic data. EMG data were rectified and smoothed using a second order low pass Butterworth Bidirectional filter (resulting in a 4th order filter) with a cut-off frequency of 14 Hz. Results: Evolution of hip, knee and ankle angle show no significant differences during the last step before touchdown, the take-off phase and the beginning of fly phase. Meanwhile, strong differences in EMG signal are noted inter and intra pole vaulter. However for a same subject the EMG activities seem to converge to some phase locked point. Discussion: All pole vaulters have approximately the same visible coordination This coordination reflects a different muscular control among pole vaulters but also for a considered pole vaulter. These phase locked point could be considered as invariant of motor control i.e. a prerequisite for a normal sequence of the movement and performance realization.